Educação permanente em saúde em unidades críticas de um hospital de ensino: elaboração de material de apoio - Valente, Drieli da Silva [UNESP] (2015)
This study has had as a general goal to elaborate supporting material for planning and performing measures in permanent education in nursing in critical hospital units and as specific goals to describe the education practice of permanent education in nursing since the identification of necessities until actions really performed in critical hospital units inside teaching hospitals identifying both facilitators and hindered factors found by supervisory nurses to the practice of permanent education in the studied context. It was qualitative study performed in a hospital that serves as a reference recognized in health, in the countryside of São Paulo state, with the involvement of seven working nurses in supervisory duty in one of the critical units, that accepted to take part as volunteers answering to guiding questions by the means of interview according to the resolution of the National Council of Health 466/12 and decision 607.299 of the Committee on Ethics on Research. The treatment given was performed according to the Content Analyses and the outcomes represent a profile of professionals specialized in the area, females in average 30 years, working in the Institution for more than 5 years and working in supervisory function higher than 2 years. In what is related to the practice of permanent education experienced and elaborated by nurses in critical hospital unit, the emerging categories were: Origin of educative actions; developed actions; Reached Outcomes by the staff; facilitators and hidered Factors in the process; and nurses perspectives about the practice of Permanent Education in Health in Critical Units. This way, based in literature and official documents about the theme of Permanent Education in Health and, from the knowledge acquired from experiencing by supervisory nurses in critical units, it was elaborated material for planning and performing of actions in Permanent Education in Nursing in Critical Hospital Units, named ...